Culture “NIRMENIRAN” (Herbal Medicine) on Improving The Nutritional Status Of Toddlers - Wardita, Yulia; Salat, Sri Yunita Suraida; Huzaimah, Naili; Adrian, Maulana Widi; Anisa (Chakra Brahmanda Lentera Institute, 2024)
Background: The region is known for its high prevalence of malnutrition cases, making it a significant concern for public health. The local health center has noted instances of malnutrition in certain areas, prompting efforts to investigate potential contributing factors and solutions. This study aims to explore the relationship between the culture of consuming local food,